Transit accessibility, land development and socioeconomic priority: A typology of planned station catchment areas in the Greater Toronto and Hamilton Area - Farber, Steven; Grandez, Maria (Journal of Transport and Land Use, 2017)
The Greater Toronto and Hamilton Area is in the process of implementing a wide array of transit expansion projects. Despite being an important evaluator of transit efficacy, accessibility is not a typical variable included in the business cases of the local planning authorities. We address this shortcoming by computing current and future accessibility scores for each proposed transit route and station. Our results are compared against measures of availability of developable land within station catchment areas and the socioeconomic priority of populations residing within catchment areas. A typology of station types is produced via a multi-criteria analysis, and this is further used to assess the efficacy of the transit plans in meeting the redevelopment and intensification goals and social priorities in the region. We are able to conclude that significant mismatches between accessibility and developable land exist. Furthermore, there is a lack of alignment between accessibility and socioeconomic priority; however, where these two criteria align, risks of redevelopment-based gentrification are low, due to the unavailability of readily developable land in these station catchment areas.